2011
DOI: 10.1152/ajpheart.00639.2010
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of EGFR in cardioprotection and signaling responses to A1 adenosine receptors and ischemic preconditioning

Abstract: Transactivation of epidermal growth factor receptor (EGFR) may contribute to specific protective responses (e.g. mediated by δ-opioid, bradykinin, or muscarinic receptors). No studies have assessed EGFR involvement in cardioprotection mediated by adenosine receptors (ARs), and the role of EGFR in ischemic preconditioning (IPC) is unclear. We tested EGFR, matrix metalloproteinase (MMP), and heparin-binding EGF (HB-EGF) dependencies of functional protection via A1AR agonism or IPC. Pretreatment of mouse hearts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 42 publications
(77 reference statements)
6
43
0
Order By: Relevance
“…Recently, other studies have assessed EGFR involvement in cardioprotection mediated by adenosine receptors (ARs). Moreover, A1AR agonist 2-chloro-N6-cyclopentyladenosine substantially increased cardiac EGFR phosphorylation, while total expression of EGFR was unchanged (29). Our study showed that CD73 regulated EGFR expression through A2AR.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, other studies have assessed EGFR involvement in cardioprotection mediated by adenosine receptors (ARs). Moreover, A1AR agonist 2-chloro-N6-cyclopentyladenosine substantially increased cardiac EGFR phosphorylation, while total expression of EGFR was unchanged (29). Our study showed that CD73 regulated EGFR expression through A2AR.…”
Section: Discussionmentioning
confidence: 51%
“…More specific analyses confirms an essential role for EGFR in preconditioning: chronic inhibition of EGFR with AG1478 attenuates ischaemic preconditioning by 50% or more (Benter et al, 2005a); and acute inhibition of EGFR, MMP or HB-EGF negates protection via preconditioning, though no effects were observed on intrinsic I-R tolerance (Williams-Pritchard et al, 2011).…”
Section: Role In Adaptive Protection -Ischaemic Preconditioningmentioning
confidence: 92%
“…Studies in cancer cells similarly supported sequestration of active EGFR within caveolae (Abulrob et al, 2004), while there is also evidence for signalling via both caveolar and non-caveolar EGFR (with prolonged ERK1/2 activation by extra-caveolar EGFR vs. transient ERK1/2 activation by caveolar EGFR) (Rimoldi et al, 2003). Interestingly, the protective A1 adenosine receptor, implicated in preconditioning responses and shown to protect via EGFR transactivation (Williams-Pritchard et al, 2011), appears to translocate out of myocardial caveolae upon activation (Lasley et al, 2000), though there is evidence A1 activation also translocates other signal elements, including PKC, into caveolae (Yang et al, 2009).…”
Section: Cell Membrane Localisation -Membrane Rafts Caveolae and Cavmentioning
confidence: 96%
See 2 more Smart Citations